California’s forest carbon offsets buffer pool is severely undercapitalized - Badgley, Grayson; Chay, Freya; Chegwidden, Oriana S.; Hamman, Joseph J.; Freeman, Jeremy; Cullenward, Danny (Frontiers in Forests and Global Change, 2022)
California operates a large forest carbon offsets program that credits carbon stored in forests across the continental United States and parts of coastal Alaska. These credits can be sold to buyers who wish to justify ongoing emissions, including in California’s cap-and-trade program. Although fossil CO₂ emissions have effectively permanent atmospheric consequences, carbon stored in forests is inherently less durable because forests are subject to significant socioeconomic and physical risks that can cause temporarily stored carbon to be re-released into the atmosphere. To address these risks, California’s program is nominally designed to provide a 100-year guarantee on forest carbon claims based on a self-insurance program known as a buffer pool. Projects contribute credits to the buffer pool based on a suite of project-specific risk factors, with buffer pool credits retired as needed to cover carbon losses from events such as wildfire or drought. So long as the buffer pool remains solvent, the program’s permanence claim remains intact. Here, we perform an actuarial analysis of the performance of California’s buffer pool. We document how wildfires have depleted nearly one-fifth of the total buffer pool in less than a decade, equivalent to at least 95% of the program-wide contribution intended to manage all fire risks for 100 years. We also show that potential carbon losses from a single forest disease, sudden oak death, could fully encumber all credits set aside for disease and insect risks. These findings indicate that California’s buffer pool is severely undercapitalized and therefore unlikely to be able to guarantee the environmental integrity of California’s forest offsets program for 100 years.